PERANAN KEHADIRAN TERHADAP KEDISIPLINAN PEGAWAI DINAS KESEJAHTERAAN SOSIAL KABUPATEN KUTAI TIMUR - Hariyati, Tati (PREDIKSI, 2016)
The purpose of this study was to determine the role of presence in the attendance book to discipline members of Aceh in the Department of Social Welfare in the East Kutai Sangata meaning high and low employee discipline allegedly caused the attendance at attendance book that is applied in the office. Therefore, researchers hypothesized, namely "Presumably if the amount of attendance signed by an employee in the high attendance book also shows high employee discipline".Research carried out on employees with two variables, namely the presence of an employee with a proven presence as an independent variable and discipline as the dependent variable. To obtain the data used questionnaire technique presented to 20 employees who constitute the study population, because in this study did not use sampling for the study population or census.Based on statistical analysis with Pearson product moment correlation formula then known price r = 0.589 which is interpreted as a moderate correlation (enough), meaning that there is significance between attendance and discipline employees at the Social Welfare Office in East Kutai. To prove the truth of the hypothesis, the researchers tested the hypothesis by using t-test formula, the test results then know that the confidence level of 0.01 to test one side and 0.02 for two-sided tests turned out t table is = 2.528 while the value t-count = 14.370, which means bigger t-count of the t-table, so that it can be concluded that the hypothesis put forward is accepted or proven, in other words, the presence was instrumental to discipline an employee at the Social Welfare Office at the East Kutai Regency.